2021
DOI: 10.1186/s13098-021-00674-z
|View full text |Cite
|
Sign up to set email alerts
|

The association of insulinemic potential of diet and lifestyle with the risk of insulin-related disorders: a prospective cohort study among participants of Tehran Lipid and Glucose Study

Abstract: Background We aim to assess the association of empirical dietary (EDIH) and lifestyle (ELIH) index for hyperinsulinemia with the risk of insulin resistance, hyperinsulinemia, insulin sensitivity, and β-cell dysfunction in Iranian adults. Methods In this prospective study, a total of 1244 men and women aged ≥ 20 years were selected among participants of the Tehran lipid and glucose study and followed for 3.2 years. Dietary intakes were assessed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(31 citation statements)
references
References 36 publications
5
25
1
Order By: Relevance
“…In the current study, we showed that higher ELIH score, determined by the combination of insulinemic potential of diet, physical activity, and BMI, are strongly associated with increased risk of two abnormal types of phenotypes, including MHO and MUO. Our results are in agreement with the findings of other studies that investigated the association of insulinemic potential of lifestyle with metabolic disorders [ 18 ]. Farhadnejad et al have shown that a higher score of ELIH was related to an increased risk of diabetes by 89% [ 18 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In the current study, we showed that higher ELIH score, determined by the combination of insulinemic potential of diet, physical activity, and BMI, are strongly associated with increased risk of two abnormal types of phenotypes, including MHO and MUO. Our results are in agreement with the findings of other studies that investigated the association of insulinemic potential of lifestyle with metabolic disorders [ 18 ]. Farhadnejad et al have shown that a higher score of ELIH was related to an increased risk of diabetes by 89% [ 18 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in agreement with the findings of other studies that investigated the association of insulinemic potential of lifestyle with metabolic disorders [ 18 ]. Farhadnejad et al have shown that a higher score of ELIH was related to an increased risk of diabetes by 89% [ 18 ]. Also, it has previously been reported that adherence to a lifestyle with a higher score of ELIH may be associated with an increased risk of insulin metabolism-related disorders, including IR, insulin insensitivity, and hyperinsulinemia [ 18 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations